Cooperation between somatic mutations and germline susceptibility variants in tumorigenesis – a dangerous liaison - Grünewald, Thomas G. P. (Mol Cell Oncol, 2015)
High-throughput genotyping and sequencing generate comprehensive catalogs of inherited genetic variations and acquired somatic mutations. However, their possible interactions and roles in tumorigenesis remain largely unexplored. We recently reported cooperation between the EWSR1-FLI1 (Ewing sarcoma breakpoint region 1 – Friend leukemia virus integration 1) fusion oncogene and a germline variant that regulates the EGR2 (early growth response 2) Ewing sarcoma susceptibility gene via a GGAA-microsatellite.